Epigenetic mechanisms in health and disease: BCEC 2017. Issue 3 (4th March 2018) - Carbonell, Albert; Fueyo, Raquel; Izquierdo-Bouldstridge, Andrea; Moreta, Cristina; Jordan, Albert
ABSTRACT: The Barcelona Conference on Epigenetics and Cancer (BCEC) entitled "Epigenetic Mechanisms in Health and Disease" was held in Barcelona, October 26-26, 2017. The 2017 BCEC was the fifth and last edition of a series of annual conferences organized as a joint effort of five leading Barcelona research institutes together with B-Debate. This edition was organized by Albert Jordan from the Molecular Biology Institute of Barcelona (IBMB-CSIC) and Marcus Bushbeck from the Josep Carreras Leukaemia Research Institute (IJC). Jordi Bernués, Marian Martínez-Balbás, and Ferran Azorín were also part of the scientific committee. In 22 talks and 51 posters, researchers presented their latest results in the fields of histone variants, epigenetic regulation, and chromatin 3D organization to an audience of around 250 participants from 16 countries. This year, a broad number of talks focused on the epigenetic causes and possible related treatments of complex diseases such as cancer. Participants at the 2017 BCEC elegantly closed the series, discussing progress made in the field of epigenetics and highlighting its role in human health and disease.